Language Analysis of Official Power in Educational Facilities Revitalization Policies on Online News Media - Nadhifatur Rizqien; Muh. Fadhalani Tafdila Syamsul; Martutik Martutik; Anang Santoso (Universitas Negeri Makassar, 2026)
This study aims to analyze how state officials’ language of power is constructed and conveyed in online news media in reporting the National Education Facility Revitalization policy and its supporting programs. This study employs a qualitative approach with a critical descriptive design, using Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA), which examines textual practices, discursive practices, and social practices. The data consist of news articles published by national online news portals, selected through purposive sampling. The findings indicate that: (1) at the textual level, power is constructed through three strategies, namely the use of technocratic diction, the legitimation of governmental authority and its right to exercise power, and the presentation of quantitative targets to create an impression of objectivity within the discourse; (2) at the level of discursive practice, political elites control discourse resources, resulting in the media primarily functioning as a channel for reproducing the government’s discourse, while community groups are marginalized and their perspectives on the actual conditions in disadvantaged, frontier, and outermost (3T) areas receive limited representation; and (3) at the level of social practice, the discourse reinforces a top-down policy structure shaped by the ideology of developmentalism. Therefore, the discourse surrounding the policy in online media functions as a means of legitimizing the government’s role and shaping public acceptance, while simultaneously limiting the visibility of critical perspectives and the complexity of conditions at the local level.